The Effect of Health Promotion With Video Media on Knowledge and Behavior About Anemia in Pregnant Mothers - Silvia Pratiwi; Sri Nabawiyati Nurul Makiyah; Farida Kartini (Syntax Corporation Indonesia, 2022)
Anemia can hurt pregnant women and fetuses. Pregnant women who experience anemia can cause complications during pregnancy and childbirth. The impact on pregnant women is the labor process that takes a long time, bleeding, and shock due to contractions. Adverse effects on the fetus are premature birth, low birth weight, damage to the placenta, mental development problems, and stillbirth. This study aims to review the evidence related to the effect of health promotion with video media on knowledge and behavior about anemia in pregnant women. The Scoping review uses the Framework from Arksey and O'Malley, which focuses on the review with the PEOS framework, conducts literature searching databases and relevant gray literature, selects relevant studies using inclusion and exclusion criteria, conducts critical appraisals to assess article quality, performs data extraction, analyze and report results. 8 literature were selected and had Grade A. Results of scoping review Factors that influence anemia in pregnant women are age, education, occupation, and parity. Health promotion can increase knowledge and behavior about anemia in pregnant women. Risk factors for anemia have an impact on pregnant women and fetuses. Based on the results of the scoping review, it was found that gaps in this study were about health promotion with video media about anemia in pregnant women more than the influence of knowledge on factors that influence anemia in pregnant women, namely education, influence, and behavior, and the impact of anemia on pregnant women. There are still few studies examining the impact of anemia on the fetus. Factors that affect anemia in pregnant women are age, education, occupation, and parity. Health promotion can increase knowledge and behavior about anemia in pregnant women. Risk factors for anemia have an impact on pregnant women and fetuses. Suggestion: It is necessary to apply policies to reduce the incidence of anemia in pregnant women and provide programs to prevent anemia in pregnant women.